Myocardial salvaging effects and mechanisms of metformin in experimental diabetes - Borde, Manjusha K.; Mohanty, Ipseeta Ray; Maheshwari, Ujwala; Suman, Rajesh Kumar; Deshmukh, Y. A. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Several epidemiological studies have found that in type II diabetic patients, Metformin improves vascular function and reduces cardiovascular events and mortality by mechanisms that are not entirely attributed to its anti- hyperglycemic effects; So far the effect of Metformin on experimentally induced myocardial infarction in setting of type II diabetic rats has not been studied. The aim of the present study was to investigate potential cardioprotective effects and mechanisms of Metformin subsequent to isoproterenol induced myocardial infarction in the setting of diabetes. Methods: Diabetes was induced with single dose of Streptozotocin (STZ): 45mg/kg ip and myocardial infarction was produced by administering isoproterenol (ISP): (85mg/kg, sc) to rats 24 and 48 h prior to sacrification (5th week). After the confirmation of diabetes on 7th day (Glucose>200mg/dl), Metformin (100 mg/kg) was administered and various parameters like anti-diabetic (Glucose, HbA1c), cardioprotective (CPK-MB, hs-CRP), metabolic (lipid profile, artherogenic potential), antioxidant (MDA) safety pancreatic function (lipase), liver function (SGPT), kidney function (Creatinine) and histopathological indices of injury were evaluated in experimental groups. Results: Administration of STZ-ISP resulted in a significant decrease in body weight (p<0.001), diabetic changes (increase in blood glucose, HbA1c), cardiac injury (leakage of myocardial CPK-MB), altered lipid profile, anti-inflammatory, antioxidant, lipase, SGPT, creatinine levels (p<0.01) in the Diabetic- ISP Control group rats as compared to Normal Control. Metformin (100 mg/kg) treatment demonstrated significant antidiabetic as well as myocardial salvaging effects as indicated by restoration of blood glucose, HbA1c and CPK-MB levels (p<0.001) compared to Diabetic- ISP Control group. In addition, Metformin favorably modulated the lipid parameters (total cholesterol, triglycerides, HDL, LDL), artherogenic index; antioxidant (MDA) potential, Subsequent to ISP challenge, histopathological assessment of heart, pancreas and biochemical indices of injury confirmed the cardioprotective effects of Metformin (100 mg/kg) in setting of diabetes. Conclusions: The present study concluded that Metformin at 100 mg/kg demonstrated myocardial salvaging effects in type II diabetic rats challenged with experimental Myocardial infarction. The antioxidant, hypoglycemic, hypolipidemic and anti-inflammatory effects of Metformin may contribute to its beneficial effects.